Exploring the Role of Digital Pronunciation Tools inEnhancing English Speaking Skills: A Case Study ofFirst-year Students at Guanfoud Mohamed and Aisso ElSalleh Middle Schools in M’Sila - Ben saoucha Hassina; Dilmi Rima (جامعة محمد بوضياف المسيلة, 2025)
The rapid advancement of digital technology has significantly influenced educational practices worldwide, particularly in the field of English as a Foreign Language (EFL) instruction. In response, EFL educators have increasingly integrated digital tools into their teaching methodologies to support the development of learners’ listening and speaking skills. This study investigates the effectiveness of digital pronunciation tools in enhancing the speaking proficiency of first-year middle school students at Guanfoud Mohamed and Aissou El Salleh schools in M’Sila, Algeria. Focusing on tools such as ELSA Speak and YouGlish, the research examines their impact on pronunciation accuracy, fluency, and learner confidence. The study employs a quasi-experimental mixed-methods design, combining quantitative assessments (pre- and post-tests) with qualitative data gathered through classroom observations and teacher questionnaires. The results revealed measurable improvements in learners' oral performance, along with increased engagement and motivation. Teachers generally expressed positive attitudes toward the use of digital tools, with their perceptions shaped by factors such as technological readiness, training, and perceived usefulness. Despite these gains, the study also identified persistent challenges including limited digital literacy, inadequate infrastructure, and insufficient professional development. These findings emphasize the potential of digital tools to transform EFL instruction, particularly when strategically implemented and supported by institutional frameworks. The study concludes with practical recommendations to foster more effective integration of technology in under-resourced educational settings, aiming to create more inclusive and interactive language learning environments.
Keywords: Keywords: Digital tools; EFL instruction; ELSA Speak; Middle school education; Speaking proficiency; YouGlish